Meeting the Behavioral Health Needs of LGBT Older Adults. Issue 8 (29th May 2019) - Goldhammer, Hilary; Krinsky, Lisa; Keuroghlian, Alex S.
Abstract : Lesbian, gay, bisexual, and transgender (LGBT) older adults face an increased risk of adverse behavioral health outcomes compared with the general population of older adults, yet little attention has been given to factors contributing to these disparities or to the ways in which clinicians can address these challenges. We present the case of a 75‐year‐old widowed lesbian woman with depression to illustrate how a lifetime of exposure to discrimination and stigma can produce high levels of stress and isolation while also fostering resilience. We then offer recommendations and resources for promoting psychological health among LGBT older adults by attending to the historical and cultural forces that affect LGBT health, and by implementing inclusive policies and programming. The article concludes with suggestions for advancing research and policy to help achieve greater health equity for LGBT older adults. J Am Geriatr Soc 67:1565–1570, 2019